Chromosomal Instability but Lack of Transformation in Human Myoblast Preparations. Issue 12 (December 2014) - Bisson, Aurélie; Le Corre, Stéphanie; Joly-Helas, Géraldine; Chambon, Pascal; Demoulins, Laetitia; Jean, Laetitia; Adriouch, Sahil; Drouot, Laurent; Giverne, Camille; Roussel, Francis; Jacquot, Serge; Doucet, Christelle; et al.
Genetic alterations have recently been described as emerging during the culture of embryonic stem cells or induced pluripotent stem cells, raising concerns about their safety in future clinical use. Myoblasts are adult stem cells with important therapeutic potential that have been used in clinical trials for almost 20 years, but their genome integrity has not yet been established. Here we produced 10 human myoblast preparations and investigated their genomic stability. At the third passage, half of the preparations had a normal karyotype and half showed one to four alterations/30 metaphases. Chromosome 2 trisomy was found in 1–2/30 meta-phases and/or 2/100 nuclei by FISH in 3/10 samples, and there was no other recurrent anomaly. When prolonging cultures, these erratic abnormalities were never associated with a growth advantage. Cellular senescence was manifested in all samples by growth arrest before passage 15. Expression of TERT was always negative. Molecular analysis of individual p53 transcripts did not reveal tumorigenic mutations. CGH array (10 samples) and exome sequencing (one sample) failed to detect copy number variations or accumulation of mutations, respectively. Myoblasts did not grow either in soft agar or in vivo after injection in immunodeficient mice. Hence, occasional genomic abnormalities may occur during myoblast culture but are not associated with risk of transformation.